Constructing And Designing A Reluctance And Initiative Scale And Its Relationship To Physical Education Female Teachers Participating In Sports Competitions In Maysan Governorate - Al-Krizi, Maitham Mutair Hamidi (Jurnal Pendidikan Jasmani Khatulistiwa, 2025)
Reluctance and initiative are important psychological dimensions that influence teachers"™ participation in professional and sports-related activities. However, research on these constructs among physical education teachers remains limited. This study aimed to construct and design a scale of reluctance and initiative, as well as to examine the relationship between these two dimensions among female physical education teachers participating in sports competitions in Maysan Governorate. The researcher employed a descriptive approach with a purposive sampling method. An exploratory study was conducted involving 9 participants for the reluctance scale and 7 participants for the initiative scale, followed by a basic study applied to 47 participants for the reluctance scale and 30 participants for the initiative scale. The reluctance scale was developed based on four main axes"”self-confidence, optimism, positive thinking, and control/domination"”each consisting of 8 items (32 items in total), while the reluctance-to-participate scale contained 20 items. Statistical analyses revealed that the participating teachers demonstrated high levels of self-confidence, optimism, positive thinking, and control/domination. Significant differences were observed, and a correlation was found between the axes of reluctance and initiative. The study concludes that the constructed scales are reliable tools for assessing reluctance and initiative among physical education teachers. The findings contribute to educational and sports psychology by providing measurement instruments that can be applied not only to physical education staff but also to educators in general. It is recommended to adopt these scales for broader use and to intensify training and professional development programs to enhance teachers"™ initiative and reduce reluctance in sports participation.